(untitled) (MAUSAM, 1962)
It is found that vapour pressure decreases with height above the capillary head depending on the vapour pressure at the capillary head and the surface of the soil column. Important causes of the decrease are due to adsorptive force of the soil particles on vapour molecules and the resistive force offered by the soil particles to the passage of vapour. Combining the3e two forces, a differential equation was formed and solved to give correct values of vapour pressure at all levels within the soil column.